Affect and Characterization in Narrative Texts Written by Senior High School Students - Djatmika, Djatmika; Santosa, Riyadi; Wiratno, Tri; Sugiarti, Rara; Wibowo, Agus Hari; Sugiarti, Tati; Lianisyah, Ulfah Yanuar; Rudiansyah, Rudiansyah (UIN Salatiga, 2023)
This article discusses the attitudinal lexis representing feelings to support the process of characterization in narrative texts written by senior high school students in Plupuh, Sragen. Six best stories were selected from twenty texts produced by the students to be analyzed for their text structure and for the way the writers exploit the emotive words representing feelings to support the process of characterization for the participants in the stories. The results show that all of the writers have good skills in arranging discourse units to be a narrative text. All of the texts are structured with the obligatory discourse units for a narrative such as Orientiation, Complication, and Resolution. Furthermore, they are also good in selecting the emotive words representing feelings in the forms of Quality and Process. However, they did not have the words in the form of Comment in their stories. The language units representing feelings are distributed along the units of the narrtive texts to support the discourse functions of each unit. Overall, the exploitation of the emotive words can help the writers in the process of characterization of the participants of the stories they produced.